Skusella Freeman (Diptera: Chironomidae): new species, immature stages from Africa, Asia and Australia, and expanded distributions - Cranston, Peter S.; Tang, Hongqu (Zootaxa, 2018)
Skusella Freeman, 1961 (Diptera: Chironomidae, Chironominae), known previously from adults from Australia and Africa, is revised with extended descriptions, including for immature life stages. Skusella is diagnosed based on its type species S. subvittata (Skuse, 1889) from Australia, S. pallidipes (Kieffer, 1921) from the Afrotropical region (the only other originally included species), a second African species S. freemani Harrison, 2002, and S. silingae Tang, sp. n., newly described here from the pupa and adult males from China. The immature stages of Skusella have been known informally for several decades, notably for a characteristic fringe of setae on one or more abdominal pleurae of the pupa, shared only with newly described Paraskusella Cranston, 2018 within the Chironominae. Amongst larvae of Chironomini with 6-segmented antenna, alternate Lauterborn organs and a well-demarcated ventromentum, those of Skusella are distinguishable only with caution due to insufficient reared associations. Unassociated pupal exuviae, tentatively belonging to three unknown new species, are described informally from China, as is a larval type from Africa. Range extensions include for S. freemani, with pupae (newly described here) from Nigeria and Cameroon, at least 5000 km from the type locality in South Africa. A wider distribution of S. subvittata in Australia and Asia is revealed by extensive pupal exuviae sampled from drift.